A case report on multiseptate gallbladder clinical manifestation and treatment (Indian Journal of Case Reports, 2021)
Multiseptate gallbladder is a rare congenital abnormality, only a few cases have been reported in the literature. These gallbladders have transversely oriented septa, with or without gallstones. Most patients present with recurrent biliary pain. The patients who are symptomatic with colic pain benefit from laparoscopic cholecystectomy. We discuss a case of an 18-year-old female who has been complaining of the right upper quadrant pain for the past 12 months with normal liver functions and diagnosed with multiseptated gallbladder on ultrasound abdomen. She undergone laparoscopic cholecystectomy and intraoperative cholangiogram cannulation failed due to a small fibrotic cystic duct. Postoperatively, she had complete resolution of symptoms.